Adaptability Trial of Paspalum conjugatum Berg, Setaria splendida Stapf and Vetiveria zizanoides (L.) Nash on Aluminum Toxicity UJI ADAPTABILITAS Paspalum conjugatum Berg, Setaria splendida Stapf, DAN Vetiveria zizanoides (L.) Nash PADA TOKSISITAS .... - Jenny Rumondang; Yadi Setiadi; Iwan Hilwan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Quartz sand mining operated by PT Holcim creates the soil minerals such as aluminum (Al). Setiadi (2012) explained that Al > 3 me/100 g soil is a toxic. Problem safter mining operational PT Holcim Tbk are: 1) Al toxicity. 2) soil compaction; 3) Ca < Mg which lead to stagnant growth. The presence of Al affected root growth, signed by swelling and browning root. Reducing Al concentration needs expensive cost. Thus, other biological alternatives which more effective and cost less are needed.This research objective was to observe plant growth at media which consist of Al toxicity. Using of Paspalum conjugatum, Setaria splendida, and Vetiveria zizanoides where use as plant indicator. The treatment were concentration of micro lime and humic substances complex. The experiment conducted at factorial design.. The resulted shows performances of three grass species planted in tailing soil gave varied result. P. conjugatum was more sensitive to Al than two others, where as S. splendida and V. zizanoides were more adaptive to Al. S. splendida can reduced Al until 61.23% and combination V. zizanoides with lolime 3g/L + HSC 2.5% can reduced Al 60.03%. V. zizanoidesis and S. splendida were potential for phytoremediation (plant which can reduce toxicity in soil).Key words: Alumunium, P. conjugatum, S. splendida, V. zizanoides